Guideline for the Management Herpes Simplex 1 and Cosmetic Interventions - Vaghela, Devan; Davies, Emma; Murray, Gillian; Convery, Cormac; Walker, Lee (The Journal of clinical and aesthetic dermatology, 2021)
The Complications in Medical Aesthetics Collaborative (CMAC) is a not-for-profit organization established to promote best patient outcomes through educating clinicians who perform nonsurgical cosmetic procedures in the prevention, diagnosis, and management of complications that can arise. The organization is a global community sharing information, learning, experience, and data to promote best practice. Herpes simplex is common in the general population. The risk of reactivation due to trauma is acknowledged in the literature. Reactivation of herpes simplex 1 following cosmetic procedures is considered rare, but there are no reliable data on the incidence. Although self-limiting, symptoms can be painful and distressing for patients who have undergone a procedure to improve their appearance. Clinicians should document the steps they've taken to avoid reactivation, and should be confident in their management plan and patient care if a patient suffers a reactivation. The authors have referred to the available literature and experience to provide a user-friendly guideline to reduce risk of herpes simplex 1 reactivation through appropriate patient screening, promote accurate diagnosis and an understanding of differentials, and provide management plans for prophylaxis to minimize adverse sequalae. In cases of post-procedure outbreak, the guideline explains the management options, including patient education and support when prescription medications are not indicated.